The Effect of Communication and Motivation on Employee Performance at PT. Perkebunan Nusantara II Pagar Merbau - Rosita Purba (Enrichment : Journal of Management, 2018)
This study aims to determine the factors that consider employee behavior and to find out the dominant variables on employee performance, at PT. Perkebunan Nusantara II, merbau fence. The sample that has been softened in this research is employees who work at PT. Perkebunan Nusantara II, merbau fence. Employees can communicate well. The number of samples is calculated using the formula according to the theory of Suparmono and Haryanto, so a total sample of 138 people is obtained. The results of this study indicate that the independent variables, namely communication factors (X1), motivation factors (X2), and employee performance factors (Y), have a positive and significant effect on employee performance at PT. Perkebunan Nusantara II, merbau fence. The results of this study also indicate that the dominant variable influences employee performance. Therefore, it can be concluded that the research hypothesis which states that there is an Influence of Motivation (X1) and Communication (X2) on Employee Performance (Y) is proven to be true. To improve employee performance, it is important for the leadership to increase motivation and communication interventions to achieve the set goals.